PELIPUTAN DAN REPORTASE TELEVISI DI LOKASI BENCANA: Sebuah Pengalaman dari Erupsi Merapi 2010 - Rochimah, Tri Hastuti Nur; Junaedi, Fajar (Journal Communication Spectrum : Capturing New Perspectives in Communication, 2014)
Mount Merapi eruption in 2010 has given a valuable lesson in the journalistic reportage in the television. Information through television about the expansion happened in the mount eruption have been largely used by the public, both the impacted ones and not. The position of Indonesia which is vulnerable towards disaster, especially because its geological position which is located in the ring of fire so that natural disaster becomes an inevitable cycle, has made the study of disaster communication strategy in television broadcasting journalism practice becomes relevant to carry on. This article explores the competency standard of the journalists in the disaster  area  and  how  is  the  journalism model  of  sensitive  disaster  based  on  the journalists experience who cover the Merapi Mount eruption in 2010. The findings showed that, first, the journalism practice, particularly television broadcasting, had higher obstacles in the disaster area compared to other occasions. Second, the journalists who are sent to the disaster area should have a basic competency of journalism and knowledge competence about the disaster occurred. Disaster competence is not only a scientific disaster aspect, but also local wisdom concerning the disaster and yet the impacted domain controls. Third, teamwork becomes a significant aspect of the journalism in the disaster area. This teamwork becomes more important when the reporting is performed live. Fourth, the reporting journalists need to uphold the circumspection principle in the reportage in order the information that is delivered does not generate any panic implication to the people affected by the disaster. Last but not least, a best pervasion and reportage model of disaster is to involve the journalists in the bureau near the disaster area since they are more mastering the reporting domain and also having access to the authority around the location. To cite this article (7th APA style): Rochimah, T. H. N. & Junaedi, F. (2014). Peliputan dan Reportase Televisi di Lokasi Bencana: Sebuah Pengalaman dari Erupsi Merapi 2010 [Television Reporting in the Location of Disaster]. Journal Communication Spectrum, 4(2), 110-125